Application Of Backpropagation Neural Networks In Predicting Rainfall Data In Ambon City - Yopi Andry Lesnussa; C. G. Mustamu; F. Kondo Lembang; M. W. Talakua (International Journal of Artificial Intelligence Research, 2018)
The Artificial Neural Networks is a process of information system on certain traits which as representatives of the human neural networks. The Artificial Neural Networks can be applied in every area of human life, one of them is environment especially about prediction of climate or weather. In this research, the artificial neural network is used to predict the rainfall with Backpropagation method and using MATLAB software. The other meteorology parameters used to predict the rainfall are air temperature, air velocity and air pressure. The result showed less accuracy level is 80% by using alpha 0,7, iteration number (epoch) 10000 and MSE value = 0,0218. Therefore, the result of rainfall prediction system is accurate.